Further contribution to the knowledge of Georgian species of the Carabus Linnaeus, 1758 subgenus Neoplectes Reitter, 1885, with description of a new subspecies of C. titarenkoi Zamotajlov & Fominykh, 2014 (Coleoptera: Carabidae: Carabini) - Fominykh, Dmitriy D.; Zamotajlov, Alexandr S.; Titarenko, Andrey Yu. (Zootaxa, 2016)
Based on material collected by the authors in 2015 in Georgia, further data are provided on the distribution, ecology, and morphology of the Carabus subgenus Neoplectes Reitter, 1885. A preliminary original identification key to the known species is provided, and a new subspecies, C. (Neoplectes) titarenkoi djanoliensis subsp. nov., is described from Dzhanoli river valley. The statuses of C. (Neoplectes) lafertei Chaudoir, 1846, C. (Neoplectes) chaudoirianus Lapouge, 1909, C. (Neoplectes) martviliensis Retezár & Djavelidze, 1992, C. (Neoplectes) prunierianus Deuve, 2012, and C. (Neoplectes) titarenkoi Zamotajlov & Fominykh, 2014 are resurrected to specific. C. (Neoplectes) mellyi boulbenorum Deuve, 2015 is synonymized with the nomynotypical subspecies. A new status of the subspecies Carabus (Neoplectes) lafertei montreuilianus Deuve, 2014, stat. nov. is also proposed.